EFFECTIVENESS OF POTASSIUM CITRATE ON URIC ACID STONES AND THE FACTORS THAT DETERMINE RESPONSE TO THERAPY (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the effectiveness of potassium citrate in patients diagnosed with uric acid stones and assess the association of stone size, stone density, stone location, and urinary pH with stone clearance.METHODOLOGY: A descriptive study was conducted at SIUT, Karachi, on the sample of 196 patients aged 18 to 60 years, either gender, diagnosed with a single, non-obstructing uric acid stone, confirmed through the radiological findings to evaluate the effectiveness of potassium citrate in patients and to assess the stone size, stone density, stone location, and urinary pH with stone clearance. Data was analyzed by SPSS version 26.RESULTS: The mean age of the participants was found to be as 42.61 ± 11.17 years. Among the 196 patients, 60.2% were male, and 39.8% were female. Stone clearance was achieved in 99 patients (50.5%). The significant association between stone clearance and factors included the stone size (p =0.011), stone density (p = 0.026), urinary pH (p = 0.028), and stone location (p = 0.036).CONCLUSION: The findings of the current study reveal that potassium citrate is an effective non-invasive treatment for uric acid stones, with stone clearance influenced by size, density, location, and urinary pH. These findings emphasize the importance of patient adherence to therapy and urinary pH monitoring in optimizing outcomes. More well-controlled prospective trials are needed to validate the current findings.